Digital predistortion using modified dynamic deviation reduction‐based Volterra model. Issue 21 (1st October 2013) - He, Zhuohui; Ye, Wu; Feng, Suili
Abstract : A modified dynamic deviation reduction‐based Volterra (MDDRV) model is presented for digital predistortion of power amplifiers. The MDDRV model is a combination of the memory polynomial model and the DDRV model. The effectiveness of the MDDRV model is validated based on experimental results.